Performance of Metarhizium anisopliae‐treated foam in combination with Phytoseiulus longipes Evans against Tetranychus evansi Baker & Pritchard (Acari: Tetranychidae)1. Issue 12 (16th August 2018) - Azandémè Hounmalon, Ginette Y; Maniania, Nguya K; Niassy, Saliou; Fellous, Simon; Kreiter, Serge; Delétré, Emilie; Fiaboe, Komi KM; Martin, Thibaud
Abstract: BACKGROUND: Tetranychus evansi ( Te ) is an exotic pest of solanaceous crops in Africa. The predatory mite Phytoseiulus longipes ( Pl ) and the fungus Metarhizium anisopliae ( Ma ) are potential biocontrol agents of Te . The present study investigated the efficacy of fungus‐treated foam placed above or below the third Te ‐infested tomato leaf. The persistence of fungus‐treated foam and the performance of Pl with and without fungus‐treated foam were evaluated. RESULTS: The fungus‐treated foam was effective when Te infestation was below the third tomato leaf as no damage was recorded on any of the upper tomato leaves up to 30 days post‐treatment. However, in the control treatments, the infestation increased considerably from 9 ± 0.3% to 100 ± 0% (mean ± standard error) at 15 days post‐treatment. The reuse of the fungus‐treated foam at 15, 30 and 45 days post‐treatment resulted in 19 ± 1.4%, 25 ± 1.2% and 54 ± 2.1%, respectively, infestation by Te . The fungus‐treated foam and Pl alone were efficient, but there was no benefit to combining them for use against Te . CONCLUSION: The fungus‐treated foam is an effective method to optimise the use of Ma in screenhouse conditions. These two control agents could be integrated in an integrated pest management strategy for crop protection. However, these results need to be confirmed in large field trials. © 2018 Society of Chemical Industry Abstract : The present study investigated the efficacy of fungus‐treated foam placed above or below the third Tetranychus evansi ‐infested tomato leaf.